Growing up together: Cohort composition and child investment - Jones, Kelly M. (Duke University Press, 2014)
In sub-Saharan Africa, 60 % of child deaths are preventable by investments in child health as simple as immunizations, bed nets, or water purification. This article investigates how a household’s decisions regarding such investments are affected by the size and gender composition of a child’s cohort. I focus on a previously overlooked type of investment: nonrival, child-specific goods (club goods). I empirically estimate the response of immunization status to cohort characteristics. I carefully address the problem of endogenous fertility, which is common in cohort studies. Because most rural Senegalese households are composed of multiple nuclear families, a child’s cohort is composed of both siblings and nonsibling children. Estimating within households, I instrument cohort characteristics with those of the nonsibling (exogenous) portion. I find that children with larger (or more predominantly male) cohorts of vaccine-eligible age are significantly more likely to receive immunization. These findings suggest that children with larger cohorts may be better off in terms of club investments; this is a significant finding for child health given that many illness prevention methods are of a club good nature.